2014
DOI: 10.1021/mz5002349
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Optimization of Directed Self-Assembly of Triblock Copolymers on Chemically Patterned Substrates

Abstract: Directed self-assembly of block copolymers on chemical patterns is of considerable interest for sublithographic patterning. The concept of pattern interpolation, in which a subset of features patterned on a substrate is multiplied through the inherent morphology of an ordered block copolymer, has enabled fabrication of extremely small, defect-free features over large areas. One of the central challenges in design of pattern interpolation strategies is that of identifying system characteristics leading to ideal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 28 publications
0
63
0
Order By: Relevance
“…More recently, design approaches using inverse methods have been implemented. [8][9][10][11]18 In these cases, the forward simulation consists of a numerical engine to solve various trial morphologies by implementing, e.g., a self-consistent field theory, 69 a mean field model based on the Cahn-Hilliard equation, 10 or a theoretically informed coarse-grain model for block copolymers. 70 As before, the forward simulation is coupled to an inverse process that optimizes the parameter set in order to achieve a solution that closely approximates the targeted design.…”
Section: Directed Self-assembly Of Block Copolymer Thin Filmsmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, design approaches using inverse methods have been implemented. [8][9][10][11]18 In these cases, the forward simulation consists of a numerical engine to solve various trial morphologies by implementing, e.g., a self-consistent field theory, 69 a mean field model based on the Cahn-Hilliard equation, 10 or a theoretically informed coarse-grain model for block copolymers. 70 As before, the forward simulation is coupled to an inverse process that optimizes the parameter set in order to achieve a solution that closely approximates the targeted design.…”
Section: Directed Self-assembly Of Block Copolymer Thin Filmsmentioning
confidence: 99%
“…70 As before, the forward simulation is coupled to an inverse process that optimizes the parameter set in order to achieve a solution that closely approximates the targeted design. In this regard, our recent work 10,11,18 has shown that evolutionary strategies such as CMA-ES can be significantly faster and more efficient in finding optimized solutions than inverse methods based on Monte Carlo searches. 8,9 In a typical design task corresponding to Fig.…”
Section: Directed Self-assembly Of Block Copolymer Thin Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical pre-patterns are defined using traditional lithographic materials and processes such as 193 nm immersion or e-beam lithography at the scale of 20 nm to 40 nm. By directing the assembly of block copolymer films on the chemical pre-patterns, the overall resolution of the lithographic process may be increased by three to four-fold or more [18,19].…”
Section: Directed Self-assembly (Dsa)mentioning
confidence: 99%